The Value Relevance of Free Cash Flow per Share: Comparative Evidence from Thailand and Indonesia - Kobkanjanapued, Yodsawinkan; Tripattanasit, Pimonwan; Thongglin, Dawprasug; Supornrungcharoen, Janjao (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This artlcle aims to examine the differences in the value relevance of free cash flow per share (FCFPS) between listed companies in Thailand and Indonesia, using financial and stock price data converted to U.S. dollars from 2021 to 2024. The data analysis includes descriptive statistics, mean difference tests, correlation analysis, and multiple regression analysis. The results show that Thai companies have significantly higher average stock prices, earnings per share (EPS), book value per share (BVS), and FCFPS compared to Indonesian companies, while Indonesia demonstrates a higher GDP growth rate. Correlation analysis reveals that stock prices are strongly positively correlated with EPS and BVS, and moderately correlated with FCFPS. The regression results indicate that FCFPS has a significant positive effect on stock prices overall; however, the interaction term between country and FCFPS is significantly negative, reflecting a difference in the value relevance of FCFPS between the Thai and Indonesian stock markets. These findings suggest that while FCFPS is relevant to stock prices in both countries, its influence and role differ depending on the context of each capital market. The study provides valuable insights for investors, policymakers, and researchers seeking to understand the role of FCFPS in stock price determination within ASEAN equity markets.